A sensitive and reliable dopamine biosensor was developed based on the Au@carbon dots–chitosan composite film - Huang, Qitong; Zhang, Hanqiang; Hu, Shirong; Li, Feiming; Weng, Wen; Chen, Jianhua; Wang, Qingxiang; He, Yasan; Zhang, Wuxiang; Bao, Xiuxiu (Biosensors & bioelectronics, 2014)
A novel composite film of Au@carbon dots (Au@CDs)–chitosan (CS) modified glassy carbon electrode (Au@CDs–CS/GCE) was prepared in a simple manner and applied in the sensitive and reliable determination of dopamine (DA). The CDs had carboxyl groups with negative charge, which not only gave it have good stability but also enabled interaction with amine functional groups in DA through electrostatic interaction to multiply recognize DA with high specificity, and the Au nanoparticle could make the surface of the electrode more conductive. Compared with the bare GCE, CS/GCE, and CDs–CS/GCE electrodes, the Au@CDs–CS/GCE had higher catalytic activity toward the oxidation of DA. Furthermore, Au@CDs–CS/GCE exhibited good ability to suppress the background current from large excess ascorbic acid (AA) and uric acid (UA). Under the optimal conditions, selective detection of DA in a linear concentration range of 0.01–100.0μM was obtained with the limit of 0.001μM (3S/N). At the same time, the Au@CDs–CS/GCE was also applied to the detection of DA content in DA's injection with satisfactory results, and the biosensor could keep its activity for at least 2 weeks. •The Au@carbon dots were used for good electrochemical signal with good biocompatibility.•Highly sensitive and selective detection of dopamine by the Au@CDs–CS/GCE.•This method was applied to the detection of DA content in its injection with satisfactory results.